1994
DOI: 10.1021/ed071p309
|View full text |Cite
|
Sign up to set email alerts
|

The Introduction of Lasers into the Physical Chemistry Curriculum

Abstract: Rationale and implementation for introducing lasers into the physical chemistry curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…There are two possible mechanisms for this reaction, associative or dissociative. 1 However, previous studies have demonstrated that for some aromatic solvents the reaction of Cr(CO) 5 (solvent) (solvent = benzene, fluorobenzene) with piperidine proceeds through a dissociative mechanism (12,13):…”
Section: (Piperidine) + Benzenementioning
confidence: 99%
See 1 more Smart Citation
“…There are two possible mechanisms for this reaction, associative or dissociative. 1 However, previous studies have demonstrated that for some aromatic solvents the reaction of Cr(CO) 5 (solvent) (solvent = benzene, fluorobenzene) with piperidine proceeds through a dissociative mechanism (12,13):…”
Section: (Piperidine) + Benzenementioning
confidence: 99%
“…The reduction in the price of lasers has made it possible to introduce laser-based experimentation into the undergraduate chemistry curriculum. As several authors have convincingly and eloquently argued, it is imperative that undergraduate students be exposed to the amazing chemistry made possible by this device (1,2). Fortunately, several chemistry experiments that use lasers have been developed for undergraduate students (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a great deal of recent and continuing interest in the introduction of lasers into the modern undergraduate teaching laboratory (1)(2)(3)(4)(5)(6). In the physical chemistry laboratory, in particular, a great deal of emphasis has been placed on the use of lasers to introduce chemistry majors to modern experimental techniques and to communicate to them the excitement associated with the new tools available to research chemists.…”
mentioning
confidence: 99%
“…Raman spectroscopy is discussed in detail in our physical chemistry lecture course, and it seemed appropriate to include a Raman experiment in the laboratory. Many articles concerning the modernization of the physical chemistry laboratory curriculum and the introduction of laser spectroscopy have appeared in this Journal (1)(2)(3)(4)(5) and other sources (6).…”
mentioning
confidence: 99%